2021
DOI: 10.14314/polimery.2021.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose from agricultural waste as an emerging material for nanotechnology applications – an overview

Abstract: It has been shown that in the last decades nanotechnology plays a key role not only in science but more and more often in industry as well. Recent research has shown that agricultural waste is a possible feedstock to produce  nanocellulose  which can be used for different applications, such as a biosensor, semiconductor and reinforcing agent. The use of agro-waste as a precursor not only offers advantages for raw material costs, but also for the climate, low processing costs, availability and convenience. It a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Different agricultural and food wastes have been used as a carbon source for the production of BNC [93][94][95][96]. With respect to the use of residual biomass from the banana value chain, rotten banana [83], as well as banana peel [44,81], have been used as a carbon source in the fermentation stage to obtain this biopolymer.…”
Section: Rs Glmentioning
confidence: 99%
“…Different agricultural and food wastes have been used as a carbon source for the production of BNC [93][94][95][96]. With respect to the use of residual biomass from the banana value chain, rotten banana [83], as well as banana peel [44,81], have been used as a carbon source in the fermentation stage to obtain this biopolymer.…”
Section: Rs Glmentioning
confidence: 99%
“…Another alternative to produce nanocellulose is through the use of microorganisms such as Gluconacetobacter xylinus or Medusomyces gisevii . Banana residues are used as a food source for the bacteria that produce bacterial nanocellulose (BNC) when the organic substrate (sugar, fructose, glycerol) is polymerized during cultivation [ 155 , 156 ].…”
Section: Use Of Banana Waste-lossmentioning
confidence: 99%
“…From the thorough study of the literature, it is found that adsorption study is the best practice to remove lead ion concentration. The adsorbent is made up of agricultural waste such as poplar, maize, rice straw wheat straw, cotton straw, cotton stalk, rice husk, coconut core, etc (Abdullah et al, 2021;Mehanny et al, 2021;S. Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%